Loss of correction in cubitus varus deformity after osteotomy. Issue 49 (10th December 2021) - You, Chao; Zhou, Yibiao; Han, Jingming
Abstract : Abstract: We aimed to investigate the rate of loss of correction and the factors thereof in pediatric patients undergoing osteotomy for treatment of cubitus varus deformity. Between July 2008 and July 2017, we treated 30 patients who underwent osteotomy for cubital varus. We compared the preoperative and postoperative clinical and imaging findings, including the H-Cobb and Baumman angles, in all patients. Postoperative evaluation was performed by telephonic interviews. Our patients consisted of 17 males and 13 females. The mean age was 75 months. At the first follow-up, approximately 80% of patients had experienced a loss of correction of the humerus-cobb angle (H-Cobb angle); at the second follow-up, the incidence was 83%. Meanwhile, 57% and 43% of patients experienced a loss of correction of the Baumman angle at the first and second follow-ups, respectively. The average interval between the first and second follow-ups was 24 days, and the mean loss in the H-Cobb angle was 2.4°. There was a significant difference between the H-Cobb angles as measured before and after surgery ( P  < .05). There was no significant difference between the H-Cobb angles of the affected side and the contralateral healthy elbow at the third postoperative follow-up; however, there was a significant difference between the Baumman angle between before and after surgery ( P  < .05). The Baumman angles as measured at the second and third postoperative follow-ups differed significantly from those of the contralateral healthy elbow joint. According to the survival curve analysis, the median survival times of the H-Cobb and Baumman angles were 27 and 34 months, respectively. The postoperative loss of the 2 angles occurred mainly during the first and second follow-up periods. Therefore, patient follow-up is particularly important in the period directly following the operation. Additional measures may be necessary to avoid rapid angle loss.